Penyuluhan Keperawatan Jiwa: Peran Keluarga Dalam Mencegah Kekambuhan Pasien Skizofrenia Di Puskesmas D - Arini, Larasuci; Nurlela, Lela; Kirana, Sukma Ayu Candra; Anggraini, Novita; Rahim, Abdul (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Mental health is an essential aspect of community well-being. Schizophrenia is a chronic psychiatric disorder that frequently relapses without adequate family involvement. This community service activity aimed to enhance family understanding and skills in preventing relapse among schizophrenic patients through a mental health nursing education program at Puskesmas D. The methods included lectures, group discussions, care demonstrations, distribution of educational leaflets, and evaluation using pre- and post-tests. The activity involved 20 families of schizophrenic patients registered at Puskesmas D. The results showed an 85% increase in knowledge after the program and improved family participation in monitoring treatment and patient behavior. This activity highlights the importance of mental health nursing education in empowering families to prevent relapse in schizophrenic patients.